PRODUKSI DAN PENDAPATAN USAHATANI PADI DI DESA PUJO ASRI KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Handayani, Siti Asih; Effendi, Irwan; Viantimala, Begem (Jurnal Ilmu-Ilmu Agribisnis, 2017)
This research aimed to find out the productivity of hybrid rice and non-hybrid rice, factors affecting hybrid rice and non-hybrid rice production, the value or R/C and B/C ratio, and farm income difference between hybrid and non-hybrid rice.  This research was taken place purposively in Pujo Asri Village of Trimurjo Sub District for this village had sufficiently high rice productivity compared to other villages.  The samples of 60 respondents were drawn by simple random sampling technique, they were 30 hybrid and 30 non-hybrid rice farmers.  The data was analyzed statistically by Cobb-Douglas production function model, income analysis and income difference test.  The results of research showed that the mean productivity of Mapan 05 variety-hybrid rice was 15.02 ton/ha per year, and that of Ciherang variety-non hybrid rice was 13.36 ton/ha per year.  The affecting factors on hybrid rice production were land width (X1), labor (X2), and application level of panca usaha tani (five principles of agribusiness) (X3), while the factors affecting the non-hybrid rice production were land width (X1), and labor (X2).  The value of R/C ratio on hybrid rice farming was 1.55 and the non-hybrid rice was 1.56.  The B/C ratio was 0.48 in wet season and 0.44 in gadu season (transition from wet to dry).  The mean income of twice farming seasons per year of hybrid rice was IDR24,809,205.33 and that of non-hybrid rice was IDR23,001,337.25.  The result of different test analysis shows that there was no significant difference between the average income of hybrid and non-hybrid rice farming on 95 percent confidence level.Key words: farming income, hybrid rice, non-hybrid rice, productivity